Pathogen spectrum and immunotherapy in patients with anti-IFN-γ autoantibodies: A multicenter retrospective study and systematic review - Qiu, Ye; Fang, Gaoneng; Ye, Feng; Zeng, Wen; Tang, Mengxin; Wei, Xuan; Yang, Jinglu; Li, Zhengtu; Zhang, Jianquan (Frontiers in Immunology, 2022)
Background: Anti-interferon-γ autoantibody (AIGA) positivity is an emerging immunodeficiency syndrome closely associated with intracellular infection in individuals without human immunodeficiency virus (HIV). However, the information on epidemiology, pathogen spectrum and immunotherapy among these patients lack a systematic description of big data. Methods: This systematic literature review and multi-center retrospective study aimed to describe the pathogen spectrum and review treatment strategies among patients with AIGA positivity. Results: This study included 810 HIV-negative patients with AIGA positivity infected with one or more intracellular pathogens. Excluding four teenagers, all the patients were adults. The most common pathogen was nontuberculous mycobacteria (NTM) (676/810, 83.5%). A total of 765 NTM isolates were identified in 676 patients with NTM, including 342 (44.7%) rapid grower mycobacteria, 273 (35.7%) slow grower mycobacteria, and 150 (19.6%) unidentified NTM subtype. Even with long-term and intensive antimicrobial treatments, 42.6% of patients with AIGA positivity had recurrence and/or persistent infection. Sixty-seven patients underwent immunoregulatory or immunosuppressive therapy, and most (60 patients) achieved remission. The most common treatment strategy was rituximab (27/67, 40.3%) and cyclophosphamide (22/67, 32.8%), followed by cyclophosphamide combined with glucocorticoids (8/67, 11.9%). Conclusions: Intracellular pathogen was the most common infection in patients with AIGA positivity. The predominant infection phenotypes were NTM, varicella-zoster virus, Talaromyces marneffei, and Salmonella spp., with or without other opportunistic infections. AIGA immunotherapy, including rituximab or cyclophosphamide, has yielded good preliminary results in some cases.